Increased carotid intima–media thickening and antioxidized low-density lipoprotein in an anti-Ro60 SLE autoantibody subset - Kurien, Biji T.; Fesmire, James; Nath, Swapan K.; Scofield, R. Hal (Frontiers in Lupus, 2023)
Objective Premature atherosclerosis is associated with systemic lupus erythematosus (SLE). We have previously shown an association of anti-Ro60/La/Ro52 with antioxidized low-density lipoprotein (LDL) in SLE. Here, we hypothesized that carotid intima–media thickening (CIMT) would be associated with antioxidized LDL (anti-oxLDL)/antilipoprotein lipase (ALPL) in a specific SLE autoantibody subset (anti-Ro60 positive, anti-RNP positive, anti-SmRNP positive, or extractable nuclear antigen antibody negative). Methods We carried out a case-control study (one time-point testing) of CIMT, ALPL, anti-oxLDL, anti-low density lipoprotein (ALDL), and anti-LDL in 114 SLE patients and 117 age/sex-matched controls. The levels of total cholesterol, LDL, high-density lipoprotein (HDL), triglycerides, and HDL-Trig were also measured. A student's t-test was used for statistical analysis. Results Interestingly, the level of CIMT was highest in the SLE subset with anti-Ro60 (23/114). CIMT and anti-oxLDL were statistically significantly elevated in the anti-Ro60 SLE subset (1.3 ± 1.66, p < 0.01; 0.26 ± 0.16, p < 0.002, respectively) compared with controls (0.54 ± 1.26; 0.165 ± 0.13, respectively), but not anti-LPL/anti-LDL. CIMT was significantly elevated (0.9 ± 1.71; p < 0.05) in the SLE subset without antiextractable nuclear antigen (ENA) (63/114) compared with controls. The other antibodies in this subset were not statistically different from other SLE subsets or controls. Only antioxLDL was significantly elevated (0.29 ± 0.27; p < 0.005) in the SLE subset with anti-RNP (14/114) compared with controls, while none were elevated in the anti-SmRNP subset (6/114). We did not find any significant differences in lipids between the various SLE subsets. Conclusion CIMT segregates in anti-Ro and ENA negative groups either with or without anti-oxLDL. It will be clinically important if cardiovascular events are augmented in the SLE anti-Ro subset having elevated antioxidized LDL antibodies.